Тhe features of using PR and advertising in international business - Iryna Derid; Karina Bozhko; Inna Zorianska (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм)
In international business, the planning of international PR and advertising campaigns is complicated by the presence in different countries of such variables as: the political and economic system of the country, the level of development of the country, the type of media system, unique culture. The subject of research in the article is the necessary adaptations of international public relations and advertising depending on the countries of business implementation. The goal of our research is to reveal how information about the specifics of the country where international business is conducted can be used to develop effective advertising and PR strategies. The objectives: to define common and different in local and international relations with the public; to investigate the feasibility of using digital or non-digital advertising and PR tools in certain countries; to consider the causes of reputational risks of international corporations; to investigate the impact of advertising on the consumer through rational and emotional methods of influence, as well as informational and transformational motivation, depending on the type of product and the level of purchase risk; to combine the effects of advertising with the characteristics of culture. General scientific methods are used: a statistical method for studying trends in the use of the Internet and social networks, as well as for researching the ratios of different types of advertising in advertising expenditures in different countries of the world; the case study method for researching advertising and PR campaigns; methods of analysis, synthesis, and descent from the abstract to the concrete to link advertising influences and cultural characteristics. The following results were obtained: something common and different in local and international PR was determined; it was found that the choice of digital PR and advertising tools should be based on the development of Internet and social media usage in a certain  country; it is determined that demonstrating respect for culture and sustainability is critically important in modern PR and advertising campaigns; it was found that the characteristics of the product and the associated purchase risk determine the methods of advertising influence, but the cultural characteristics of the target audience determine specific methods of advertising. Conclusions: only a detailed study of the country for which the advertising and PR strategies are intended makes it possible to achieve the desired effect. At the same time, the study of ads of international corporations for different countries based on the overlay of applied methods of influence on the cultural characteristics of these countries confirms that companies really use these approaches in practice.